The role of glucagon-like peptide-1 receptor (GLP-1R) agonists in enhancing endothelial function: a potential avenue for improving heart failure with preserved ejection fraction (HFpEF) - Darshan Hullon; Ghasaq K. Subeh; Yelizaveta Volkova; Karolina Janiec; Adam Trach; Ruslan Mnevets (Cardiovascular Diabetology)
Abstract Heart failure with preserved ejection fraction (HFpEF) is a prevalent and complex condition with limited effective treatments. Endothelial dysfunction is a significant component of HFpEF pathophysiology, and glucagon-like peptide-1 receptor (GLP-1R) agonists have shown potential benefits in improving endothelial function. This study aims to explore the relationship between endothelial dysfunction in HFpEF and the mechanisms of action of GLP-1R agonists, highlighting their potential therapeutic benefits. A comprehensive review of the literature was conducted to examine the etiology of HFpEF, the role of endothelial dysfunction, and the effects of GLP-1R agonists on endothelial function and heart failure outcomes. The findings indicate that HFpEF is associated with various comorbidities, such as obesity, diabetes mellitus, and hypertension, which contribute to endothelial dysfunction. GLP-1R agonists, including semaglutide and liraglutide, have demonstrated significant cardioprotective effects, such as improving vascular endothelial function, reducing inflammation, and preventing atherosclerosis. Clinical trials, such as the STEP-HFpEF trial, have shown positive results in reducing symptoms and physical restrictions in HFpEF patients. GLP-1R agonists present a promising therapeutic option for HFpEF by targeting endothelial dysfunction and other pathophysiological mechanisms. Further research is needed to elucidate the precise mechanisms through which GLP-1R agonists exert their benefits and to establish their long-term safety and efficacy in diverse HFpEF populations.